2021
DOI: 10.1101/2021.06.21.449242
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of the key role of white matter alteration in the pathogenesis of Huntington’s Disease

Abstract: Pathogenesis of the inherited neurodegenerative disorder Huntington s Disease (HD) is complex and progressive, with a long presymptomatic phase in which subtle changes occur in the brain of gene carriers up to 15 years before the onset of symptoms. Thus, there is a need of early, functional biomarker to better understand disease progression and to evaluate treatment efficacy far from onset. In particular, recent studies have shown that white matter may be affected early in HD. In this study, we scanned longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…To further demonstrate JAK2ca beneficial effects on clinically-relevant pathological outcomes, we next performed magnetic resonance imaging. Eighteen month-old heterozygous Hdh140 mice display significant striatal atrophy 46 , likely due to the atrophy of striatal neurons themselves 47 , and not to their death, as neuronal loss was described only in older homozygous Hdh140 mice 43 . Striatal volume can be measured accurately with T 2 -weighted magnetic resonance imaging 48 , and striatal atrophy is observed at prodromal stages in Huntington's disease patients 49 .…”
Section: Activation Of Jak2-stat3 Pathway In Astrocytes Is Beneficial...mentioning
confidence: 95%
“…To further demonstrate JAK2ca beneficial effects on clinically-relevant pathological outcomes, we next performed magnetic resonance imaging. Eighteen month-old heterozygous Hdh140 mice display significant striatal atrophy 46 , likely due to the atrophy of striatal neurons themselves 47 , and not to their death, as neuronal loss was described only in older homozygous Hdh140 mice 43 . Striatal volume can be measured accurately with T 2 -weighted magnetic resonance imaging 48 , and striatal atrophy is observed at prodromal stages in Huntington's disease patients 49 .…”
Section: Activation Of Jak2-stat3 Pathway In Astrocytes Is Beneficial...mentioning
confidence: 95%
“…Perot et al reported that there was no variation of corpus callosum volume in the CAG140KI mice by using DTI assay, which showed that FA values in CAG140KI mice are only reduced in the first 8 months compared to WT. This difference becomes rather insignificant over time [ 55 ]. Others also reported the absence of white matter changes in the Hdh (CAG) 150 mouse brain using MRI study [ 56 ].…”
Section: Evidence Of White Matter Defects In Mouse Modelsmentioning
confidence: 99%
“…Images were co-registered and automatically segmented using an in-house python library Sammba-MRI [ 17 ], as already described [ 18 ]. Metabolites concentration were estimated with LCModel [ 19 ] using default pipeline, and was normalized by total creatine (tCr).…”
Section: Methodsmentioning
confidence: 99%